Strategies and criteria targeting the reform and development for the teaching resource of nursing undergraduate: A multi-center cross-sectional study. Issue 20 (21st May 2021) - Liu, Chang-qing; Wei, Yi; Ren, Hong-fei; Zhou, Qian; Chen, Juan; Guo, Hong-xia; Li, Xiao-ling; Ni, Zhao; Cao, Xiao-yi; Li, Ka; Li, Ji-ping
Abstract : Abstract: Teaching resource of nursing students play an important role in improving clinical performance, while there is a little know and dearth of the access and development criteria or guidance of teaching resources for nursing undergraduates. To develop the admission and development criteria of education resources for nursing undergraduates, and to explore and determine its composition and connotation. A cross-sectional survey has been used. A total of 22 Chinese nursing schools and affiliated teaching bases (hospitals and community health centers). A total of 20 nursing experts were consulted to develop the questionnaire of admission and development criteria of teaching resource for nursing undergraduates in China, and then 285 valid experts from 22 Chinese nursing schools and affiliated teaching bases (hospitals and community health centers) conducted the questionnaire survey to evaluate experts' consensus rate and view on the composition and connotation of the developed criteria. There were 6 domains and 43 items included in the admission and development criteria of teaching resource for nursing undergraduates, which domains included educational budget and allocation of resources, infrastructure, clinical teaching bases, books and information services, educational experts, and educational exchanges. The experts' consensus rate was more than 90.2%. The standard is helpful to guide the future admission and development of teaching resource for nursing undergraduates, and favor the education quality improvement of nursing undergraduates.